PENGARUH FLASH SALE, PRICE DISCOUNT DAN TAGLINE “GRATIS ONGKIR” TERHADAP PERILAKU IMPULSIVE BUYING KONSUMEN SHOPEE (Studi pada Konsumen Shopee di Ciledug, Kota Tangerang) - Sucipto, Denny; Niazi, Hakam Ali (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to identify and analyze the influence of Flash sale, Price discount, and "Free Shipping" Tagline on the impulsive buying behavior of Shopee consumers in Ciledug, Tangerang City. The research employed a quantitative method using a multiple regression approach to analyze data collected through Likert-scale questionnaires processed using Microsoft Excel 2016 and SPSS version 22. The results indicate that Flash sale and Price discount significantly and positively influence impulsive buying behavior, while the "Free Shipping" Tagline also has an influence but to a lesser extent compared to the other two variables. Based on these findings, e-commerce companies like Shopee are recommended to continue optimizing their Flash sale and Price discount promotion strategies, while maintaining the use of the "Free Shipping" Tagline as part of their marketing strategy